The study of brand awareness and brand loyalty of intention to purchase case: UniFi / Nur Syuhadah Masron - Masron, Nur Syuhadah (2017)
Intention to purchases refers to the willingness of a customer to buy a certain product or certain service. In general, there are numbers of factors to determine the influenced of the intention to purchases. This research has provided an insight on two variables which are brand awareness and brand loyalty towards intention to purchase on TM products, case: UniFi in Temerloh. There are 100 respondents were chosen to complete this research, by answering a 100 set of questionnaire. The results obtained that the factors that influenced intention to purchase is significantly relationship towards the variable.